ANALISIS PRICE DISCOVERY SAHAM ALIBABA DI NYSE DAN HKEX - Rosyanti, Novi; Syahwani, Asty Khairi Inayah; Ginoga, Lesia Fatma; Ramadhanti, Resti Jayeng; Saleh, Rahmat; Firmansyah, Iman (Politeknik Ubaya, 2025)
This research analyzes the price discovery process of Alibaba shares traded on two major exchanges: the New York Stock Exchange (NYSE) with the ticker BABA and the Hong Kong Exchange (HKEX) with the ticker 9988. The methods used include the Vector Error Correction Model (VECM), Hasbrouck's Information Share (IS), and Impulse Response Function (IRF) to measure the relative contribution of each exchange in reflecting new information in stock prices. The results of the analysis show that the two exchanges have a strong long-term relationship, as indicated by the Johansen cointegration test. Based on the IS calculation, HKEX has a greater contribution to price discovery compared to NYSE, indicating that Alibaba's stock price reflects new information faster on HKEX. The IRF analysis shows that price shocks on one exchange have a significant impact on the other exchange in the short term, but the effect tends to diminish in the long term. These findings provide insight for investors in choosing a more efficient exchange for transactions and open up arbitrage opportunities based on the different roles of each exchange in price discovery.